The Psychologist's Companion / A Guide to Scientific Writing for Students and Researcher's - Stenberg Robert J (Cambridge University Press, 2006)
A definitive guide to scientific writing for students and researchers. Acknowledgements, Introduction, Eight Common Misconceptions about Psychology Papers, Steps in Writing the Library Research Paper, Steps in Writing the Experimental Research Paper, Rules for Writing the Psychology Paper, Using the Internet to Aid the Research Process, Commonly Misused Words, American Psychological Association Guidelines for Psychology Papers, Guidelines for Data Presentation, References for the Psychology Paper, Standards for Evaluating the Psychology Paper, Submitting a Paper to a Journal, Writing a Grant or Contract Proposal, How to Find a Book Publisher, Writing a lecture, Article Writing, References, Index.